Pengaruh Meaningful, Joyful, dan Mindful Learning Sebagai Pilar Deep Learning terhadap Hasil Belajar: Literature Review - Ade Ramadhan (JPT : Jurnal Pendidikan Tematik, 2025)
This study aims to examine the role of meaningful, mindful, and joyful learning approaches as pillars of deep learning in improving student learning outcomes. Using a qualitative approach through literature review, this study analyzed various articles and books discussing each approach and their integration. The results of the study indicate that meaningful learning helps improve students' critical thinking skills, reading comprehension, activeness, and writing skills by linking new knowledge to existing experiences. Mindful learning encourages self-awareness, concentration, creativity, and collaboration skills through a reflective learning process, enabling students to be fully present and actively engaged. Meanwhile, joyful learning has been shown to improve students' affective aspects, such as motivation, enthusiasm, participation, and attention, which indirectly support improved cognitive abilities and conceptual understanding. The integration of these three approaches has been shown to improve students' motivation, language skills, conceptual understanding, and self-awareness, resulting in a more holistic and in-depth learning process. Therefore, educators are advised to implement these three approaches in an integrated manner to create an effective, enjoyable, and meaningful learning environment. Further research can be conducted to test their practical implementation across various classroom contexts and educational levels.